Spatial relationship between well water arsenic and uranium in Northern Plains native lands. (15th October 2021) - Sobel, Marisa; Sanchez, Tiffany R.; Zacher, Tracy; Mailloux, Brian; Powers, Martha; Yracheta, Joseph; Harvey, David; Best, Lyle G.; Bear, Annabelle Black; Hasan, Khaled; Thomas, Elizabeth; Morgan, Camille; et al.
Abstract: Arsenic and uranium in unregulated private wells affect many rural populations across the US. The distribution of these contaminants in the private wells of most American Indian communities is poorly characterized, and seldom studied together. Here, we evaluate the association between drinking water arsenic and uranium levels in wells (n = 441) from three tribal regions in North Dakota and South Dakota participating in the Strong Heart Water Study. Groundwater contamination was extensive; 29% and 7% of wells exceeded maximum contaminant levels for arsenic and uranium respectively. 81% of wells had both arsenic and uranium concentrations at one-tenth of their human-health benchmark (arsenic, 1 μg/L; uranium 3 μg/L). Well arsenic and uranium concentrations were uncorrelated ( r s = 0.06); however, there appeared to be a spatial correlation of wells co-contaminated by arsenic and uranium associated with flow along a geologic contact. These findings indicate the importance of measuring multiple metals in well water, and to understand underlying hydrogeological conditions. The underlying mechanisms for the prevalence of arsenic and uranium across Northern Plains Tribal Lands in the US, and in particular the occurrence of both elevated arsenic and uranium in drinking water wells in this region, demands further study. Graphical abstract: Image 1 Highlights: Drinking water of American Indian communities is poorly characterized. 29% and 7% of wells exceeded maximum contaminant levels (MCL) for As and U. Co-contaminated wells by As and U associated with flow along a geologic contact. Approximately 60% of wells exceed As MCL, 20% U MCL, at <5 km from the contact.